Governance without Government in the MENA Region (Springer Nature, 2025)
This open access volume offers a timely and original contribution to scholarships in the Middle East and North Africa by focusing on governance and public policy in post-conflict contexts. Unlike works that center primarily on conflict and geopolitics, Governance without Government examines how authority is exercised in fragmented and transitional settings. Drawing on diverse case studies, the book explores informal governance, hybrid institutions, and the evolving roles of state and non-state actors across the MENA region. Each chapter of the book delves into specialized and focused realms, presenting a lucid, cohesive, and compelling narrative. Tailored to cater to upper-level undergraduates and postgraduates specializing in the politics, international relations, and political economy of the MENA region, it also offering valuable insights for research degrees homing in on country-specific or thematic case studies. The interdisciplinary and international appeal ensures its relevance on reading lists globally, extending beyond North America and the United Kingdom. Setting itself apart in terms of originality and composition, this book stands out amid a decade since the Arab Spring, distinguishing itself from a limited pool of comparable titles. The amalgamation of empirical and theoretical approaches enhances its worth, rendering it an indispensable resource for policy-oriented graduate students, researchers, and professionals immersed in or focusing on the MENA region and Africa. The chapters carve out new territory, both conceptually and empirically, offering insights that are not only groundbreaking but also highly applicable in navigating the intricate landscapes of governance in conflict-affected areas. As the MENA region confronts novel policy challenges, our book encapsulates a snapshot of case studies and the wellspring of policy-relevant concepts and ideas. Addressing lingering issues post-2011, it lays the groundwork for these regions to progress in a more sustainable manner. "Governance without Government" transcends by being a mere book; it evolves into a guide for comprehending and shaping the future of governance within the ever-changing landscape of the MENA region. About the Editor: Moosa Elayah is Associate Professor of Public Administration at the Doha Institute for Graduate Studies. His work focuses on governance, civil society, and post-conflict institutional development in the MENA region.